Improving Learning Outcomes in Writing Short Story Text through Project Based Learning Model in Class XI.5 SMA IT ICBS Payakumbuh - Azmi, Winda; Rahmadani, Nurul (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
This study aims to determine the improvement of student learning outcomes in writing short story texts using project-based learning models in class XI.5 SMA IT Insan Cendekian Boarding School Payakumbuh. this research method is Classroom Action Research. The data of this study were collected using field notes, observations, interviews, test results, and documentary evidence in cycles I and II. The data obtained were analyzed using percentage analysis. The results of this study indicate that the use of project-based learning models can improve student learning outcomes in writing short story texts. This is evidenced by the increase in the completeness of learning outcomes in each cycle, in the pre-cycle student learning outcomes of 33%, cycle I of 56%, and in cycle II learning outcomes have reached 100%. The novelty of this research lies in the application of the Project Based Learning (PjBL) model which is tailored to the specific needs of IT ICBS Payakumbuh High School students to improve learning outcomes in writing short story texts. Its contribution is to provide an alternative learning strategy that is effective and applicable in developing students' writing skills at the secondary school level